Guided-Inquiry of Green Chemistry-Based Experiments in Biodiesel Synthesis - Risnita Vicky Listyarini; Fransisca Ditawati Nur Pamenang; Noer Kurnia Dewi (Scientiae Educatia: Jurnal Pendidikan Sains, 2020)
The use of non-renewable energy sources such as fossil fuels is very contrary to the concept of sustainable development. The principles of green chemistry can be applied to laboratory work through experiments based on environmental issues such as energy. Biodiesel is an alternative fuel to replace fossil fuels which can be made through the process of transesterification of oils. This research aims to apply the principles of green chemistry in biodiesel synthesis experiments; designing and conducting thoughtful and efficient experiments; characterizing biodiesel products and knowing students' responses to green chemistry-based experiments in biodiesel synthesis. The results showed that the principles of green chemistry were successfully applied in the synthesis of biodiesel. Biodiesel products have a bright yellow colour, pH of 7, and density between 0.866-0.892 g/mL. Water contents range from 1.67-3.3, and acid numbers range from 0.69-4.3. 90/10 tests show the results between range 0.5-3% and kinematic viscosity from 4.195-4.995. Students showed a positive response of 75.36% in designing experimental procedures for greenchemistry-based biodiesel synthesis.